The Importance of Sign Language in Media for the Deaf in Times of Crisis (for example, Covid-19) - Abdullah, Muzaffar Jabbar; Ali, Karwan Moamen; Suleiman, Nayan Aziz; Mohammed, Sarwat Abdullah (Sulaimani Journal for Humanities, 2025)
Crises create imbalances in normal situations and pose a risk to human life or to organizations and institutions. During sudden and unforeseen natural crises such as floods, hurricanes, earthquakes, and volcanoes, or humanitarian crises such as economic crises, terrorism, wars between two countries or political parties, diseases, and pandemics such as COVID-19, the crisis-related parties play the most important role in crisis management and control, in order to restore balance to the situation in which they are found and to protect the safety of the people in the crisis area in all its aspects. The coronavirus pandemic 2019 (COVID-19) has established itself as a global health crisis due to its rapid spread and strong impact in a very short period of time, and has had a profound impact on the way we perceive the world and our daily lives. Not only did the rate of infection and mode of transmission jeopardize our sense of security, but the safety measures put in place to control the spread of the virus, such as social distancing, limiting face-to-face social interactions, and avoiding essentially human and basic necessities of life, have changed people's daily routines. There are many reasons and measures that must be taken to control and manage any crisis. One of the most important measures is communication because, without creating a communication network, it is not easy to convey messages to the people around the crisis area or to ensure awareness of safety, security, and information about the crisis. Therefore, there is a strong connection between crises, crisis management, and communication during crises, and television is one of the most effective communication channels. It plays an important role in this. Crisis management teams can deliver information, guidance, and news to citizens through television and raise awareness. Society is made up of many different classes, and each stratum has its own needs, just as crisis managers must know their stakeholders and provide them with information according to their needs (Ulmer, Sgott, & Seeger, 2012). Similarly, the media should send messages to a group during times of crisis according to the needs of that class. There are a number of people with disabilities in Kurdistan who have their own unique needs, including the deaf community, which relies on sign language to communicate with others. At the end of the study, we concluded that the presence of sign language during the COVID-19 crisis was important for the deaf, but the Kurdish media did not adequately address this issue, so the deaf considered themselves a marginalized group in society during the crisis.
Keywords: Media; media roles; articles; crisis; COVID19